The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15255/kui.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Mechanical-Electrochemical Characterisation of Open Cell Antimonial-lead Foams Made by the “Excess Salt Replication Method” for Eventual Applications in Lead-acid Batteries Manufacturing

Abstract: In this study, open cell 25 % antimony-lead alloy foams are fabricated for possible use to lighten thick plates of lead-acid batteries. A new inexpensive and simple variant of the salt replication process is developed and explored. Different morphology and shapes have been successfully obtained with “excess salt replication” method (abbreviated as ESR method). Best porosity of about 68 % is obtained with salt particles size of about 3 mm. SEM and EDXS investigation of the composite salt/antimony alloy before N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, it is also important to ensure a uniform distribution of sodium chloride particles throughout the volume of metal materials and the thermal preparation of the sodium chloride itself. A similar method for the production porous materials (lead alloys with antimony) using sodium chloride was carried out by the authors of [20]. Results concerning the production of samples of porous aluminium materials with the same shape (from aluminium alloy AlSi12 and four sizes of sodium chloride particles: 1 to 3 mm, 3 to 5 mm, 5 to 7 mm and 8 to 10 mm) confirmed that the proposed and verified methodology is suitable for production.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, it is also important to ensure a uniform distribution of sodium chloride particles throughout the volume of metal materials and the thermal preparation of the sodium chloride itself. A similar method for the production porous materials (lead alloys with antimony) using sodium chloride was carried out by the authors of [20]. Results concerning the production of samples of porous aluminium materials with the same shape (from aluminium alloy AlSi12 and four sizes of sodium chloride particles: 1 to 3 mm, 3 to 5 mm, 5 to 7 mm and 8 to 10 mm) confirmed that the proposed and verified methodology is suitable for production.…”
Section: Discussionmentioning
confidence: 70%
“…The most common method is infiltration of the metal melt, also known as the replication process [18]. The authors of [20] applied sodium chloride to produce lead-based porous materials with some amount of antimony (25 wt%) for the purpose of producing grids for electric batteries. The authors refer to this method used to produce porous materials as the Excess Salt Replication Method (ESR method).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 represents the ESR process steps to produce zamak 5 foams with porosities ranging from 58% to 65% and a salt grain size between 2.5 mm and 4.5 mm. This process has been attempted successfully with alloys of good fluidity and low melting temperature (below that of salt), such as a 25% antimony-lead alloy [11] and the zamak 5 alloy of this study. The four steps of this method are: metal fusion, excess salt compaction, cooling, and salt leaching.…”
Section: Experimental Processmentioning
confidence: 99%
“…In this paper, the air flow through open-cell foams resulting from a new variant of the salt replication process was used in order to gain insight on their morphology (mesostructure). This process, which belongs to the space holder technics, was named "excess salt replication process" (abbreviated as ESR Process) [11]. Different forms and shapes of cellular materials with different alloys have been successfully fabricated with this process.…”
Section: Introductionmentioning
confidence: 99%
“…These foams were made available through a new variant of the space holder replication technique developed using salt (NaCl) as a removable preform. This variant was named the Excess Salt Replication process (ESR process) [41]. In order to obtain samples of good quality, metals and alloys of good castability are highly recommended, like the 25% antimonial lead alloy (25% Sb-Pb), among others, which can give samples of porosity between 46% and 66%.…”
Section: Introductionmentioning
confidence: 99%